El concepto de ciudadanía - Todd, Roberto H. (My University, 1942)
Discurso pronunciado ante la Logia Cosmo.
Keywords: Freemasonry--Puerto Rico.; Masoneria--Puerto Rico.; Self-determination, National--Puerto Rico.; Autodeterminación, Nacional--Puerto Rico.